Measures of Anxiety Disorder Symptoms in Adolescents. - Martinez-Snyder, Anna E.; Valentiner, David P.; Mick, Cassandra R. (Child Psychiatry & Human Development, 2025)
This study examines select psychometric properties (i.e., internal reliability, and factorial, convergent, discriminant, and criterion validity) of three commonly-used measures of anxiety disorder symptoms in adolescents in the context of multi-trait, multi-method matrix analyses. A sample of 331 adolescents (age M = 17.1; 75.3% white; 71.0% female) completed three self-report scales that assess symptoms of separation anxiety, social anxiety, panic, and generalized anxiety, as well as measures of depression, experiential avoidance, and intolerance of uncertainty. Measures of panic disorder symptoms showed poor factorial, convergent, and discriminant validity. A multi-trait, multi-method matrix model to understand the relationships among the measures of separation anxiety, social anxiety, and generalized anxiety symptoms provided a reasonable fit to the data. Measures of separation anxiety showed poor discriminant and criterion validity, suggesting limited relevance of separation anxiety in this adolescent sample. Measures of social anxiety generally showed evidence of adequate-to-good factorial, convergent, and discriminant validity. Measures of generalized anxiety showed adequate –to-good factorial and convergent validity, and poor-to-adequate discriminant validity. The associations of measures of social and generalized anxiety with measures of depression, experiential avoidance, and intolerance of uncertainty were at least partially independent of method variance. The findings of this study add to the growing literature that evaluates the strengths and limitations of these scales for clinical practice and research.